Design of Umrah Registration Information System PT Amanah Wisata Group using Waterfall Method - Setyanto, Rangga; Setiaji, Pratomo; Muzid, Syafiul (Sistemasi: Jurnal Sistem Informasi, 2025)
This study aims to replace the manual registration system still used by PT Amanah Wisata Group with a web-based digital system. Previously, 80% of the registration process was conducted manually, often leading to errors and delays, including having to wait up to two working days to receive registration forms. The research methodology includes the collection of primary data through interviews with administrative staff and direct observation of the registration process, as well as secondary data from literature reviews and relevant documentation. The system development follows the Waterfall method, consisting of requirement analysis and system design using Unified Modeling Language (UML). The registration system also integrates a Customer Relationship Management (CRM) approach to foster stronger relationships with prospective pilgrims, improve two-way communication, and enable faster and more accurate delivery of Umrah package information and notifications. The results show that the developed system consists of three main modules: an online registration module, a pilgrim data management module, and a payment module. This system enhances administrative efficiency, reduces data entry errors, improves staff performance, and strengthens customer interaction. In conclusion, the web-based information system combined with a CRM approach not only supports the digital transformation of Umrah services but also enhances service quality and the overall experience of prospective pilgrims.